Republican discourse and organicism topic in peruvian journalistic opinion columns about political corruptions facts - Pisconte Quispe, Alan Martín (2023)
This paper analyzes the importance about the presence of certain republican discourse concepts. Terms such as organism or nation body, are used frequently in some peruvian journalistic opinion columns about political corruptions facts recently. Some of them were made for political and bureaucratic agents belonging to peruvian political system. In this study, the author claims that there are reasons to believe in a republican discourse persistence in analyzes that journalist do of this quotidian political corruption’s facts. Although this persistence has been object of historical and philosophical studies in Europe, America, and Latin-American, in Peru is yet not so frequently discussed. This paper aims to make a contribution in regard to this subject.